2014
DOI: 10.1177/1062860614555430
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Quality Improvement Conference

Abstract: The Veterans Healthcare Administration (VA) has embraced patient safety and quality improvement in the quest to improve care for veterans. The New Mexico VA Health Care System introduced a new morbidity and mortality conference, called the Interdisciplinary Quality Improvement Conference (IQIC), using patient case presentations to focus on underlying systems in the clinical care environment. The revised conference design also effectively teaches the 6 Accreditation Council for Graduate Medical Education (ACGME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 10 publications
3
26
0
Order By: Relevance
“…In short, this study pointed to the importance of making sure M&M attendees are motivated to participate and take action, well-informed to identify targets and plans for improvement, and willing and able to realize plans that ensue from the meeting. More specific success factors highlighted in this surgical study, which were also found in studies in other medical settings, include the importance of resources (i.e., time and staff), 20,21 leadership buy-in and presence, 21,22 input from all staff levels, [20][21][22][23] and loop closure. 20,22 In the wider literature on organizational learning and implementation science, the importance of individual and team factors is frequently stressed since, after all, "culture eats strategy for breakfast."…”
Section: Insights From Mandm Literature: Structural and Cultural Factorssupporting
confidence: 58%
See 1 more Smart Citation
“…In short, this study pointed to the importance of making sure M&M attendees are motivated to participate and take action, well-informed to identify targets and plans for improvement, and willing and able to realize plans that ensue from the meeting. More specific success factors highlighted in this surgical study, which were also found in studies in other medical settings, include the importance of resources (i.e., time and staff), 20,21 leadership buy-in and presence, 21,22 input from all staff levels, [20][21][22][23] and loop closure. 20,22 In the wider literature on organizational learning and implementation science, the importance of individual and team factors is frequently stressed since, after all, "culture eats strategy for breakfast."…”
Section: Insights From Mandm Literature: Structural and Cultural Factorssupporting
confidence: 58%
“…More specific success factors highlighted in this surgical study, which were also found in studies in other medical settings, include the importance of resources (i.e., time and staff), 20,21 leadership buy-in and presence, 21,22 input from all staff levels, [20][21][22][23] and loop closure. 20,22 In the wider literature on organizational learning and implementation science, the importance of individual and team factors is frequently stressed since, after all, "culture eats strategy for breakfast." [24][25][26] Even though the literature commonly highlights the need for an atmosphere free of "shame and blame" at the conference, 13,[27][28][29][30] it remains poorly understood how exactly to establish or support this.…”
Section: Insights From Mandm Literature: Structural and Cultural Factorssupporting
confidence: 58%
“…Selecting invested leaders and champions from within the department fosters better systems change in similar efforts, perhaps due to their direct involvement in the front lines as a partial stakeholder in the effort. 16,17,29,30 Examples of QI efforts that have been identified thus far include reevaluation of how preoperative urine cultures are collected in our clinic and a new workflow for perioperative anticoagulation management. Further research into changes in patient safety, morbidity, and mortality following the intervention is warranted, and will be an ongoing process as we track and follow up on initiatives derived through our improved process.…”
Section: Discussionmentioning
confidence: 99%
“…Expanding on the idea of obtaining input from multiple sources, several institutions have recognized that expanding the M&M review to a broader, interdisciplinary audience has allowed for better identification of systems-based issues (18,19,27). However, as noted by the Lucian Leape Institute, traditional M&M meetings often fall short of their potential, in part because they fail to include the patient’s point of view (28).…”
Section: Introductionmentioning
confidence: 99%
“…Given the ACGME mandate, there has been widespread adoption of the M&M conference across US hospitals (16). Given its prevalence, the M&M review has the potential to significantly influence patient care and quality improvement (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%